The valorization of neem leaves infused coconut oil at various concentrations for the production of natural liquid shampoo - Rini Nurul Fauziyah; Asri Widyasanti (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2021)
The liquid shampoo is a product that is generally used to clean hair and scalp. The additional active ingredient used in the liquid shampoo is neem leaves which contain polyphenols that have antibacterial effects. Neem leaves extract was made by hot infusion method with coconut oil as a solvent. The purposes of this research were to find the best concentration of neem leaves infused oil for liquid shampoo material and compare the qualities of liquid shampoo with Indonesian National Standard (SNI) of Shampoo 06-2692-1992. The method of this research was a laboratory experiment with descriptive analysis. This research was conducted in five treatments. Concentration neem leaves infused oil for liquid shampoo materials were ratio between coconut oil and neem leaves in sample A = 720:0 (w/w); B = 720:22,5 (w/w); C = 720:30 (w/w); D = 720:45 (w/w); and E = 720:90 (w/w). The result showed that all of the shampoos met the SNI of Shampoo 06-2692-1992 according to organoleptic, moisture content, and pH. The best shampoo based on organoleptic observation was shampoo C (720:30 (w/w)) with a hedonic percentage of 40%, moisture content of 69.89%, pH 7.03, and specific gravity of 1.0223 g/g. The highest antibacterial activity against S. aureus was shampoo E (720:90 (w/w)) with an inhibition zone diameter was 9.5 mm. Shampoo with the highest antibacterial activity resulted from the highest addition of coconut oils infused Neem leaves. It proved that neem leaves were effective as an additive in making shampoo to boost its antimicrobial properties.